Algal assays and monitoring eutrophication - Marvan, P. | Pribil, S. (Alemania | ALEMANIA Germany, 1979)
Contents: Problems of eutrophication and its estimation; theoretical principles of algal testes; Selection of organisms and their precultivation
Sin Especificar
Keywords: Algas | Eutrofización